A Contrastive Terminological Exploration of the French Term ‘‘âme’’ through its various Translations in the Jerusalem Bible - AKPACA, SERVAIS MARTIAL (My University, 2018)
Abstract – The aim of this research work is to show that the French term âme is a polysemous word that has a wide lexical field inthe English version of the Jerusalem Bible. Indeed, the English version of the Bible reveals many equivalents of the term. It actually refers to a very wide concept. The research methodology is both descriptive and analytical in the sense that every single occurrence of the term in the French version of the bible is compared with its English translation and every new sense is discussed and analysed. This approach leads to the conclusion that every context in which the term is used influences its meaning. Indeed, the words spirit, mind, soul, heart, etc., have been identified as equivalents of the term âme in the bible. In a nutshell, the term âme is of undeniable terminological interest. Résumé – Le but de cette recherche est de montrer que le terme français âme est un mot polysémique dont le champ lexical est très étendu dans la version anglaise. En effet, la version anglaise de la bible révèle un grand nombre d‟équivalents du terme. En réalité, le concept auquel il renvoie est d‟une grande portée. La méthodologie de recherche est à la fois descriptive et analytique en ce sens que chaque occurrence du terme dans la version française de la bible est comparée à sa traduction en anglais et chaque nouveau sens fait l‟objet de discussion et d‟analyse. Cette approche nous amène à conclure que chaque contexte dans lequel le terme est utilisé influence son sens. En effet, les mots spirit, mind, soul, heart, etc., ont été identifiés comme étant des équivalents du terme âme dans la bible. En conclusion, le terme âme est d‟un intérêt terminologique indéniable.
Keywords: âme; term; corpus linguistics; translation